The influence of stalls (24 hours) on interest in shopping at Indomarand Alfamart - Hilya zulva; Ahmad Nuh (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This research aims to investigate the influence of the availability of 24-hour stalls on interest in shopping at Indomart and Alfamart. The survey method was carried out by distributing questionnaires to visitors to the two stalls in XYZ City. The results of data analysis using multiple linear regression show that the availability of 24-hour stalls has a significant positive influence on interest in shopping at both shops. Apart from that, factors such as location, price and promotions also play an important role in influencing visitors' shopping interest. The managerial implications of this research provide insight to store owners and managers to improve services and marketing strategies to attract more customers. Further research can be carried out by expanding the sample scope and considering other variables that influence visitors' shopping interest.